2019
DOI: 10.1002/cam4.2070
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 increases the stemness and is highly expressed in relapsed human hepatocellular carcinoma

Abstract: Toll‐like receptor 4 ( TLR 4) plays an essential role in cancer progress. Here, we find that the expression of TLR 4 in relapsed human hepatocellular carcinoma ( HCC ) clinical samples is higher than that in the non‐relapsed ones, which leads us to explore the role of TLR 4 in cancer stemness. We reported that TLR 4‐ AKT signaling pathway was activated by lipopolysaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 41 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…More and more evidences show that LPS plays a role in the development of HCC. Zhou et al 344 found that LPS activates the TLR4–AKT–SOX2 signaling pathway of liver cancer cell lines to improve the ability of cancer stem cells; Lin et al 345 found that there is a positive feedback loop of COX-2/PGE2/signal transducer and activator of transcription factor 3 (STAT3) activated by LPS in liver cancer cells, which regulates the expression of genes related to tumor proliferation, differentiation, and apoptosis. In the latest research on the treatment of liver cancer, it is found that the antitumor effect of TLR9 agonist combined with anti-PD-1 antibody or anti-PD-L1 is significantly better than single-agent therapy.…”
Section: Prr-related Diseasesmentioning
confidence: 99%
“…More and more evidences show that LPS plays a role in the development of HCC. Zhou et al 344 found that LPS activates the TLR4–AKT–SOX2 signaling pathway of liver cancer cell lines to improve the ability of cancer stem cells; Lin et al 345 found that there is a positive feedback loop of COX-2/PGE2/signal transducer and activator of transcription factor 3 (STAT3) activated by LPS in liver cancer cells, which regulates the expression of genes related to tumor proliferation, differentiation, and apoptosis. In the latest research on the treatment of liver cancer, it is found that the antitumor effect of TLR9 agonist combined with anti-PD-1 antibody or anti-PD-L1 is significantly better than single-agent therapy.…”
Section: Prr-related Diseasesmentioning
confidence: 99%
“… 10 Toll-like receptor 4 (TLR4)/Akt signalling was shown to promote cancer stemness in HCC cell lines, as reflected by an increase in the CD133 + CD49 + HCC cell population, by upregulating Sox2. 20 The enhanced tumorigenicity of CD133 + CD49 + HCC cells was also Nanog dependent, 21 as CD133 + Nanog high cells had increased expression of insulin-like growth factor 2 (IGF2) mRNA-binding protein-3 and YAP1, which ultimately inhibited transforming growth factor-β (TGF-β) signalling from suppressing TLR4 signalling. 21 …”
Section: Markers For Cancer Stemness In the Livermentioning
confidence: 99%
“…More importantly, Zhou et al proved that TLR4 expression was substantially upregulated in tumor tissues from HCC patients compared to adjacent tissues (Yao et al 2018 ). In addition, other research has demonstrated the promotive role for TLR4 in the development of HCC cells, and TLR4 inhibition was shown to have strong effects on LPS-induced inflammation and HCC cell proliferation (Lin et al 2016a ; Zhou et al 2019 ). Similar to these studies, the results in our studies suggested that RTF could significantly inhibit the expression of TLR4, as well as the activation of the NF-κB pathway, in HCC cells, which resulted in the suppression of various malignant behaviors of HCC cells.…”
Section: Discussionmentioning
confidence: 99%